Validation of Linear Range HER2/Estrogen Receptor/Progesterone Receptor IHControls for Daily Quality Assurance. Issue 3 (13th February 2023) - Sompuram, Seshi R; Vani, Kodela; Ryan, Lori; Johnson, Corissa; Szabolcs, Matthias; Peruyero, Leonore; Balaton, André; Pierrot, Sandrine; Joseph, Lija; Pilichowska, Monika; Naber, Stephen; Goldsmith, Jeffrey; et al.
Abstract: Objectives: To evaluate a new US Food and Drug Administration (FDA)–cleared immunohistochemistry (IHC) control (IHControls [Boston Cell Standards]) comprising peptide epitopes for HER2, estrogen receptor (ER), and progesterone receptor (PR) attached to cell-sized microspheres and to compare its performance against conventional tissue controls. Methods: IHControls and tissue/cell line controls for HER2, ER, and PR were compared side by side daily at 5 clinical IHC laboratories for 1 to 2 months. Separately, the sensitivity of the 2 types of controls was evaluated in simulated IHC assay failure experiments by diluting the primary antibody. Additional evaluations included lot-to-lot manufacturing reproducibility of 3 independent lots and specificity against 26 antigenically irrelevant IHC stains. Results: Side-by-side testing revealed a 99.6% concordance between IHControls and tissue controls across 5 IHC laboratories and 766 individual evaluations. Three discordant quality control events were the result of operator error. Simulated assay failure data showed that both IHControls and tissue controls are similarly capable of detecting IHC staining errors. Manufacturing reproducibility of IHControls showed less than 10% variability (coefficient of variation). No cross-reactions were detected from 26 antigenically irrelevant IHC stains. Conclusions: IHControls, the first FDA-cleared IHC controls, can sensitively and accurately detect IHC assay problems, similar to tissue controls.